Mild Deglobalization: Foreign Investment Screening and Cross-Border Investment - Vera Z. Eichenauer; Feicheng Wang (CESifo GmbH, 2024)
Openness to foreign investments is associated with national security risks. To mitigate these risks, many high-income countries have strengthened the control of foreign investments in an increasing number of sectors considered security-sensitive. However, this policy may deter foreign investments and thereby affect the economy negatively. This is the first cross-country panel study to examine how investment screening affects cross-border investments. We combine data on cross-border mergers and acquisitions (M&As) for the period 2007-2022 with information on sectoral investment screening by 43 OECD or EU countries. Using a staggered triple differences design, we estimate that investment screening leads to an average reduction of 12 to 16 percent in the number of M&A deals. The negative impact is driven by minority acquisitions with an acquired stake below 50 percent. The findings call policymakers' attention to weighing the benefits of national security against the unintended economic costs of broad investment screening policies.
Keywords: F21; F52; G34; 330; foreign direct investments; national security; investment screening; geoeconomic fragmentation; deglobalization